MONITORING THE QUALITY OF CLEAN WATER TREATMENT IN THE WATER TREATMENT PLANT FILTRATION UNIT USING THE BACKWASH METHOD - Halim, Abdul; Fatah, Ryan Nur (Sustainable Environmental and Optimizing Industry Journal, 2023)
Water for an industry is a supporting material for both direct and indirect activities to support several systems. Requirements for the quality of water used in industry vary depending on its intended use. Water that comes from nature generally does not meet the necessary requirements so it must undergo a processing process first. Raw water sources play a very important role in the clean water industry. Raw water is the beginning of a process in the supply and treatment of clean water. Water Treatment Plant (WTP) or Water Treatment Plant (IPA) is a system/facility that functions to treat water from contaminated raw (influent) water to obtain the desired water quality treatment according to quality standards. The purpose of this study was to determine the effect of treated water quality and backwash effectiveness by comparing the values of chemical and physical parameters before and after the backwash process in the filtration process unit of a clean water treatment plant. After conducting the tests, it was concluded that the backwash process is very effective in maximizing the performance of a filtration process unit. The effective value of acidity (pH) is (0-5)%, hardness and turbidity is (40-50)%, total dissolved solid (TDS) is (5-10)% and conductivity is (10-20)%. This also shows that the quality of the water tested has met the quality standards in accordance with Permenkes No. 492 of 2010.